MENINGKATKAN PENJUALAN UMKM MELALUI STRATEGI PEMASARAN ONLINE YANG EFEKTIF - Latifah, Lutfatul; Mulyanti, Kurniawati; Chairunnisa, Nurlalila Maysaroh (An-Nizam, 2024)
This service aims to explore the potential of online marketing strategies in increasing sales of Micro, Small and Medium Enterprises (MSMEs) in Indonesia, with a focus on MSMEs that have not yet run online marketing. Although digital technology has developed rapidly, many MSMEs still do not maximize the potential of online marketing. The service method used is the community education method with MSME owners who have not run online marketing which will be carried out on February 19, 2024, precisely in Sukamukti Village, Bojongmangu District, Bekasi Regency to understand their challenges and needs in dealing with online marketing strategies. This service has a positive impact on understanding the barriers faced by MSMEs in starting online marketing, as well as their views on its potential and benefits. However, there is a need for support and mentoring for MSMEs that have not yet embarked on online marketing, as well as the importance of providing appropriate resources and training.